Characteristics of patients losing vision after 2 years of monthly dosing in the phase III ranibizumab clinical trials - Rosenfeld, Philip J; Shapiro, Howard; Tuomi, Lisa; Webster, Mary; Elledge, Julee; Blodi, Barbara (Ophthalmology (Rochester, Minn.), 2011)
To investigate the cause of visual acuity (VA) loss in patients with neovascular age-related macular degeneration (AMD) receiving monthly ranibizumab injections in the pivotal ranibizumab phase III trials. Retrospective analysis. The Minimally Classic/Occult Trial of the Anti-VEGF Antibody Ranibizumab In the treatment of Neovascular AMD (MARINA) and Anti-VEGF Antibody for the Treatment of Predominantly Classic Choroidal Neovascularization in AMD (ANCHOR) trials. Demographics and lesion characteristics at baseline and month 24 were compared in patients with ≥15 letters VA loss and patients with ≥15 letters VA gain from baseline to month 24. Additional evaluations of fundus photographs from these patients were performed to assess features of non-exudative AMD, such as geographic atrophy (GA) and retinal pigment epithelium (RPE) abnormalities. Differences in lesion characteristics between patients who lost versus gained ≥15 letters of VA from baseline to month 24. At month 24, 9% of ranibizumab-treated patients from MARINA and 10% of ranibizumab-treated patients from ANCHOR had lost ≥15 letters VA; 30% of ranibizumab-treated patients from MARINA and 38% of ranibizumab-treated patients from ANCHOR had gained ≥15 letters VA. Baseline characteristics associated with VA loss at month 24 included older age, better VA, and larger lesions. At month 24, an increased area of RPE abnormality was associated with VA loss in both the MARINA (P = 0.0008) and ANCHOR (P = 0.0046) trials. Increased total lesion area at month 24 was associated with VA loss in both trials. In MARINA, the increase in total lesion area was attributable to an increase in the angiographic designation of atrophic scar among VA losers (P = 0.0043), but in ANCHOR it was attributable to an increased area of choroidal neovascularization (CNV) (P = 0.039) but not an increased area of leakage (P = 0.17). Increased areas of GA, fibrosis, and hemorrhage were not associated with VA loss. Vision loss after 2 years of monthly ranibizumab therapy was associated with lesion characteristics commonly associated with suppressed CNV, such as pigmentary abnormalities, atrophic scar, and the absence of leakage. Future VA improvements in patients receiving ranibizumab therapy may require preservation of photoreceptor and RPE function rather than strategies that target CNV.